Pacific Internet Limited : seizing the future - Gleave, Tom (2013)
Pacific Internet Limited (PacNet), Singapore's second oldest and second largest Internet Service Provider (ISP), signaled a new stage in its development when it appointed Tan Tong Hai as its new CEO in February 2001. In assuming the top position at the NASDAQ-listed company, Tan's mandate was to return PacNet to profitability. Although the six-year old ISP had sustained losses in its initial years of operations, it had become profitable by 1998, as Internet usage began to explode around the world. This trend was short-lived, however, as the number of rivals in the six Asian markets in which PacNet operated began to increase substantially, thus creating significant downward pressure on prices, particularly for residential access services.